Clinical Features and Therapeutic Response in Taiwanese Children With Wilson's Disease: 12 Years of Experience in a Single Center - Li-Ching Wang; Jiaan-Der Wang; Chi-Ren Tsai; Shao-Bin Cheng; Chieh-Chung Lin (Pediatrics and Neonatology)
Wilson's disease (WD) is an autosomal recessive defect of cellular copper export. Early diagnosis in children is difficult due to its obscure clinical presentations. The efficacy of zinc salts is well documented, although there are limited data concerning zinc use in pediatric patients with WD. Methods: We performed a retrospective analysis of clinical features, laboratory results and treatment responses in children with WD diagnosed at Taichung Veterans General Hospital between 1996 and 2008. Diagnosis was established by low serum ceruloplasmin, high 24-hour urinary copper excretion, presence of Kayser-Fleischer rings, and mutation analysis. Results: Eleven children were included in this study. The main initial presentations were impaired liver function tests (6/11) and hemolytic anemia (2/11). Gene studies in seven children showed six different mutations (G934D, R778Q, C490X, 304insC, IVS4-1 G > C, P992I) and one possible novel mutation (L1181P). All patients had improved liver function tests and hemoglobin levels after treatment with D-penicillamine, trientine and zinc supplement therapy. During a mean period of 3.4 ± 2.1 years with zinc therapy, six patients had serum zinc levels above the normal limit, and seven patients had serum copper levels below the normal range. Conclusion: Serum ceruloplasmin and 24-hour urinary copper examinations could be used to rule out WD in children with chronic hepatitis and hemolytic anemia. Gene analysis is helpful for prompt diagnosis of asymptomatic siblings and patients with atypical features. Zinc treatment is generally safe in pediatric patients with WD. However, its adverse effects should be monitored.